Wax Extracted from Waste Cauliflower Leaves Shows Potential Antitranspirant Efficacy When Applied to Rapeseed Plants - Michele Faralli; Minuka Weerasinghe; Gee-Sian Leung; Ray Marriott; Melville Miles; Peter Kettlewell (Agronomy, 2022)
The stress from excessive transpiration of water from plant leaves can damage crop growth during droughts. Specific commercial biostimulant products (antitranspirants) are available to reduce transpiration when applied to plants, but these products are expensive. Antitranspirants from waste would be cheaper, and the aim of this research was to extract leaf wax from a fresh produce processing waste and conduct a preliminary evaluation of its antitranspirant efficacy. Supercritical CO2 was used to extract wax from cauliflower leaves, and after formulating for spraying, the wax was applied to young rapeseed plants in three consecutive experiments. The wax was compared with a commercially-available terpene antitranspirant (di-1-p-menthene) for efficacy in reducing stomatal conductance and water use. In two of the three experiments, stomatal conductance was significantly reduced to similar extents by wax and by di-1-p-menthene, despite the wax being formulated and applied at a much lower concentration. Water use was reduced by wax in one experiment. Further research is needed on formulation, spraying conditions, and dose-response. These preliminary results demonstrate the potential for extracted leaf wax to act as a biostimulant and ameliorate plant drought stress.